Measuring the Image of God: The God Image Inventory and the God Image Scales - Lawrence, Richard T. (Journal of psychology and theology, 1997)
The God Image Inventory (GII) is an 8-scale, 156-item, psychometric instrument to measure the image of God, developed for clinical and pastoral use in N = 1 cases. For research use with a large N, the God Image Scales (GIS), in a 6-scale, 72-item format, or a 3-scale, 36-item format, are preferred subsets of the GII. The GII and GIS are designed on the basis of Ana-Maria Rizzuto's distinction between the God concept and the God image. They explore issues of belonging (Presence and Challenge scales), goodness (Acceptance and Benevolence scales) and control (Influence and Providence scales). The scales of the GII have demonstrated internal reliability and preliminary validity work has been done. Standards have been developed on an N = 1580 sample of U.S. adults, but are applicable, at least to date, only for Christian subjects. A computerized version is expected shortly. The GIS (text in Appendix) have begun to be used by other researchers, and results to date have supported the validity of the GIS scales.